Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1021/acs.chemmater.0c00333
|View full text |Cite
|
Sign up to set email alerts
|

Li2O Solid Electrolyte Interphase: Probing Transport Properties at the Chemical Potential of Lithium

Abstract: Lithium (Li) anodes suffer numerous challenges arising from the chemically inhomogeneous nature of the native solid electrolyte interphase (SEI), which impedes smooth plating and leads to dendrite growth. In spite of much attention paid to engineering Li interfaces of late, there is still limited understanding of the desired chemical composition of an improved Li SEI. One major challenge has been a lack of empirical data on the structure-property-performance relations in individual SEI phases, and specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
107
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 57 publications
7
107
0
Order By: Relevance
“…[34] The amorphous inorganic components consist of both ceramic-like Inorg Amor , and metallic Li Amor . [35] plus interfacial diffusion along the grain boundaries and phase boundaries, should be further investigated. Reports showed that the space charge effect along the interfaces of these nanocrystalline inorganic phases can sometime generate a higher ionic carrier concentration and improves the ionic conductivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[34] The amorphous inorganic components consist of both ceramic-like Inorg Amor , and metallic Li Amor . [35] plus interfacial diffusion along the grain boundaries and phase boundaries, should be further investigated. Reports showed that the space charge effect along the interfaces of these nanocrystalline inorganic phases can sometime generate a higher ionic carrier concentration and improves the ionic conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…Reports showed that the space charge effect along the interfaces of these nanocrystalline inorganic phases can sometime generate a higher ionic carrier concentration and improves the ionic conductivity. [35,36] The success of the DTD additive is attributed to the formation of stable SEI with a gradient distribution of the organic and inorganic components that have high mechanical and chemical stability. In particular, a gradient amorphous matrix (polymeric → inorganic → metallic) with nanocrystalline embedded phases of Li 2 SO 4 , Li 2 CO 3 , Li 2 O appear to be a quite general structural model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…successfully created an artificial SEI that is consisted of pure Li 2 O. [ 37 ] After the systematic investigations on the Li 2 O SEI, it was discovered that the ionic conductivity of Li 2 O on SEI is ≈10 −9 S cm −1 at room temperature. Intriguingly, the ionic conductivity of Li 2 O SEI is three magnitudes higher than that of a sintered Li 2 O pellet (10 −12 S cm −1 ).…”
Section: Properties Of Solid Electrolyte Interphasementioning
confidence: 99%
“…It was proved that LiF, Li 2 O, and Li 2 CO 3 in native SEI diffuse Li + via grain boundaries, as their intrinsic ionic conductivity is relatively low (up to ~ 10 −9 S cm −1 ). 25, [49][50][51] Nitrides such as lithium nitride (Li 3 N) and LiN x O y have much higher ionic conductivity (up to ~ 10 −3 S cm −1 ), [52][53][54] and they can provide faster Li + migration channels in the SEI. Therefore, nitrided SEI can facilitate Li + diffusion and improve the kinetics of the Li plating process.…”
Section: Facilitating LI + Diffusion Through the Seimentioning
confidence: 99%